2016
DOI: 10.1542/peds.2015-0155
|View full text |Cite
|
Sign up to set email alerts
|

A Case of an 11-year-old With Cough, Diarrhea, and Findings of Concern in His Lungs and Spleen

Abstract: This is the case of a previously healthy, 11-year-old male of Indian descent who presented to the emergency department with a 2-month history of nausea, vomiting, diarrhea, fatigue, cough, and 7-lb weight loss. Acutely, he developed 5 days of fever as high as 39.4°C. He had a remote travel history to the Middle East. On physical examination, he was febrile and tachycardic, was thin but otherwise had a normal examination. His inflammatory markers were elevated: erythrocyte sedimentation rate was 93 mm/hour and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The keywords "pediatric", "Crohn's disease", and "pulmonary" were used to retrieve the associated literature from PubMed, and the reference lists of these identified studies were checked. The review identified 22 cases of CD with pulmonary involvement (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), which consisted of 10 males and 12 females, and the ratio of males to females was 1:1.2. The clinical manifestations, chest radiological features, and histological manifestations of these cases are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…The keywords "pediatric", "Crohn's disease", and "pulmonary" were used to retrieve the associated literature from PubMed, and the reference lists of these identified studies were checked. The review identified 22 cases of CD with pulmonary involvement (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), which consisted of 10 males and 12 females, and the ratio of males to females was 1:1.2. The clinical manifestations, chest radiological features, and histological manifestations of these cases are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%